Newspapers and information visualization - Tosete, Francisco (Anuario ThinkEPI, 2009)
The newspapers are one of the media that we use every day to inform us. Although our usual reading of them is purely textual, another much richer option exists: visual reading. Understanding the underlying patterns in the composition of the submodules in a news item, and the relationships between graphic images, modules of ads and other modules of news, gives us a much richer and interesting interpretation of our reality that is transmitted by the newspaper editors.